Recombinant protein expression in microbial systems - Rosano, German Leandro (2014)
The emergence of recombinant DNA technology during the early 70's set a revolution in molecular biology. This set of techniques was strengthened even further later on with the introduction of the polymerase chain reaction and allowed scientists to explore and understand essential life processes in an easy and straightforward way. It also marked the birth of the modern biotech industry. At that time, it was shown that eukaryotic DNA could be propagated in Escherichia coli (Morrow et al., 1974) and functional products could be synthesized from heterologous genes cloned in bacterial plasmids (Ratzkin and Carbon, 1977; Vapnek et al., 1977). After these successful cases, it was soon realized that the potential applications of these techniques were almost limitless. In fact, US patent 4,237,224 granted to Cohen and Boyer (1980) claimed to commercial ownership of the methodology for cloning virtually all possible DNAs in all possible vectors. While cloning any gene in any given vector is feasible, obtaining a functional product from its expression is not that simple.